A splicing-based multitissue association study of joint transcriptomes identified susceptibility genes for osteoarthritis - Zhang, Lantao; Zhao, Fuxing; Zhang, Hengheng; Niu, Xingbang; Li, Youliang; Zhao, Chunxia; Ding, Jianhua; Liu, Chaozheng (Frontiers in Immunology, 2025)
BackgroundOsteoarthritis (OA) is a common chronic degenerative joint disease worldwide, which seriously affects the quality of life of patients and adds economic burden. Although genome-wide association studies (GWAS) have identified multiple genetic loci associated with OA, the functional mechanisms of these loci remain unclear. Transcriptome association studies (TWAS) combining gene expression and GWAS data have provided new perspectives to explore the genetic basis of OA.MethodsThis study integrated cross-tissue and single-tissue TWAS analyses as well as single-cell sequencing data to identify and validate the key genes associated with OA. Cross- and single-tissue analyses were performed using the UTMOST, FUSION, and MAGMA methods, while single-cell sequencing was applied for the investigation of the expression characteristics, pseudotemporal trajectories, and cell-to-cell communication patterns of the latent transforming growth factor beta binding protein 1 (LTBP1) in different cell subtypes.ResultsThis study identified multiple candidate genes associated with OA, among which LTBP1 displayed a significant association in both cross-tissue and single-tissue analyses (FDR < 0.05) and was validated as a key regulator of the transforming growth factor-beta (TGF-β) signaling pathway. Single-cell sequencing revealed that LTBP1 was differentially expressed in different chondrocyte subtypes and was associated with high enrichment of the Notch signaling pathway. Pseudotemporal analysis revealed the dynamic regulatory role of LTBP1 in chondrocyte differentiation.ConclusionIntercellular communication analysis revealed that cells with high LTBP1 expression activated diverse signaling pathways such as TGF-β and vascular endothelial growth factor (VEGF), suggesting that it may be involved in the pathogenesis of OA by regulating the formation of the extracellular matrix and the immune response.